FGF21/FGFR1-β-KL cascade in cardiomyocytes modulates angiogenesis and inflammation under metabolic stress - Namrita Kaur; Sanskruti Ravindra Gare; Andrea Ruiz-Velasco; Jessica M. Miller; Riham R.E. Abouleisa; Qinghui Ou; Jiahan Shen; Handrean Soran; Tamer M.A. Mohamed; Wei Liu (Heliyon, 2023)
Diabetes is a metabolic disorder with an increased risk of developing heart failure. Inflammation and damaged vasculature are the cardinal features of diabetes-induced cardiac damage. Moreover, systemic metabolic stress triggers discordant intercellular communication, thus culminating in cardiac dysfunction. Fibroblast growth factor 21 (FGF21) is a pleiotropic hormone transducing cellular signals via fibroblast growth factor receptor 1 (FGFR1) and its co-receptor beta-klotho (β-KL). This study first demonstrated a decreased expression or activity of FGFR1 and β-KL in both human and mouse diabetic hearts. Reinforcing cardiac FGFR1 and β-KL expression can alleviate pro-inflammatory response and endothelial dysfunction upon diabetic stress. Using proteomics, novel cardiomyocyte-derived anti-inflammatory and proangiogenic factors regulated by FGFR1-β-KL signaling were identified. Although not exhaustive, this study provides a unique insight into the protective topology of the cardiac FGFR1-β-KL signaling-mediated intercellular reactions in the heart in response to metabolic stress.